The Relationship Between Parental Support and Learning Outcomes For Social Studies Package B At SPNF SKB Bukittinggi City - Chania, Yolanda; Irmawita, Irmawita (Universitas Negeri Padang, 2024)
The background to this research is the low social studies learning outcomes of residents studying package B. The aim of this research is to see a picture of the family environment of study residents, see a picture of social studies learning outcomes of residents studying package B, and see a picture of social studies learning outcomes of residents studying package B. The relationship between the family environment and Social Sciences learning results package B at SPNF SKB Bukittinggi City. This research uses a correlational quantitative approach. The population of this study was residents studying package b at SPNF SKB Bukittinggi City, totaling 45 people. Meanwhile, samples were taken from 60% of the population, namely 27 people, using a cluster random sampling technique. Data collection techniques using questionnaires. Data analysis techniques using percentage formulas and Spearman rank formulas. The research results show (1) the family environment is still not good, (2) student learning outcomes are still relatively low, (3) there is a relationship between the family environment and social studies learning outcomes package b, this relationship is declared significant because it is categorized as very strong. It is recommended that parents provide support in education in the family environment in order to optimize student learning outcomes. The SPNF SKB Institute is able to provide motivational support to learning residents and be creative in using learning media so that learning enthusiasm can increase among learning residents. Future researchers can identify characteristics or other variables that have not been examined in this research for further follow-up. Keywords: Family Environment, Learning Outcomes